2020
DOI: 10.1002/lary.28868
|View full text |Cite
|
Sign up to set email alerts
|

Adding Flexible Instrumentation to a Curved Videolaryngoscope: A Novel Tool for Laryngeal Surgery

Abstract: Objectives Transoral surgery of the larynx with rigid instruments is not always possible. This may result in insufficient therapy or in an increased need for open surgery. For these patients, alternative surgical systems are needed. Here, we demonstrate a curved prototype for laryngeal surgery equipped with flexible instruments. Study Design Pre‐clinical user study in an ex vivo porcine laryngeal model. Methods The prototype was built from established medical devices, namely a hyperangulated videolaryngoscope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…They reported a good general impression and no head and neck strain using the system with a 40-inch external monitor. The results of this user study suggest that the prototype is an interesting and low-priced alternative to the previously available systems in robotic larynx surgery, especially concerning visualization and accessibility of the operation site [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…They reported a good general impression and no head and neck strain using the system with a 40-inch external monitor. The results of this user study suggest that the prototype is an interesting and low-priced alternative to the previously available systems in robotic larynx surgery, especially concerning visualization and accessibility of the operation site [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…A detailed setup of the surgical prototype has been published before [ 10 ]. We modified a video laryngoscope for surgical purposes by equipping it with flexible dual-arm instrumentation (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We have developed a new surgical prototype, the surgical MAC system (sMAC), which could enable laryngeal diagnostics and surgical treatment even in cases of difficult laryngeal exposure [ 10 ]. The sMAC system is composed of a hyper-angulated video laryngoscope modified with flexible instruments.…”
Section: Introductionmentioning
confidence: 99%
“…The study conducted by Schild et al showed that use of an hyperangulated video laryngoscope with usage of modified flexible instruments can be cost effective and minimally invasive alternative in cases of difficult laryngeal exposure [13].…”
Section: Advantagesmentioning
confidence: 99%